Investigation of the influence of constant pressure oil source fluctuations on ultra-precision machining. (February 2015) - Chen, Wanqun; Liang, Yingchun; Sun, Yazhou; An, Chenhui; Chen, Guoda
The waviness errors on the machined surfaces have significant impact on the performance of optical components. Mid-spatial frequency errors (amplitude near 10 nm, wavelength about 1 mm) are found on the machined surfaces along feeding direction, and the oil pressure fluctuations of the hydrostatic slide are confirmed to be the main source which produces such waviness errors. In this article, the influence of oil pressure fluctuations on the machined surface is studied quantitatively for the first time, and the corresponding experiments are carried out. Besides, the three-dimensional surface profile simulations of workpieces considering the oil pressure fluctuations are achieved. The simulation results have been verified by the experiments on an ultra-precision flycutting machine.